Synthesis, characterization and electrochemical studies of Cu(II), Fe(II), Fe(III) and Ni(II) complexes of some o-phenylenediamine Schiff bases / Abdulaziz Ali Alomari - Alomari, Abdulaziz Ali (2010)
Four Schiff base ligands, N,N’-1,2-benzene-1,2-diyl-bis(5-chlorosalicylideneimine) (H2L1), N,N’-1,2-benzene-1,2-diyl-bis(4-bromosalicylideneimine) (H2L2), N,N’-1,2- benzene-1,2-diyl-bis(4-hydroxysalicylideneimine) (H2L3), and N,N’-1,2-benzene-1,2-diyl-bis(3-bromo-5-chlorosalicylideneimine) (H2L4) were obtained in good yields from the condensation reaction of o-phenylenediamine with 5-chlorosalicylaldehyde, 5-bromosalicylaldehyde, 4-hydroxysalicylaldehyde and 3-bromo-5-chlorosalicylaldehyde respectively. These Schiff bases formed complexes with copper(II), iron(II) and nickel(II) ions in good yields. The structures of these complexes are mainly square planar, which is confirmed by the crystal structure of nickel(II) complex of bis-N,N’-3-chloro-5-bromosalicylideneamine-,2-diaminobenzene. Attempts to prepare the corresponding iron(III) complexes were unsuccessful. The ligands were characterized by Fourier transform infrared spectroscopy, elemental analysis, 1H-Nuclear magnetic resonance spectroscopy and UV-vis spectroscopy, while the complexes were characterized by Fourier transform infrared spectroscopy, elemental analysis, UV-vis spectroscopy and cyclic voltammetry. H2L4 nickel(II) complex has been subjected to X-ray crystal structure analysis which reveals that the nickel atom is coordinated to two phenoxyl oxygen atoms and two imino nitrogen atoms in the cis configuration. The local coordination geometry around the nickel atom is a square planar configuration, with a rms deviation of 0.034 (1) Å from a least-squares iii plane defined by the two nitrogen, two oxygen and the nickel atoms in the molecule. The nickel atom is situated 0.003(1)Å away from this plane. The cyclic voltammetry studies showed that CuL1, CuL2, FeL2, and NiL3 may be suitable to be used as redox catalysts.